2015
DOI: 10.1007/s00438-015-1073-z
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of NF-YB family genes in tung tree

Abstract: The NF-YB transcription factor gene family encodes a subunit of the CCAAT box-binding factor (CBF), a highly conserved trimeric activator that strongly binds to the CCAAT box promoter element. Studies on model plants have shown that NF-YB proteins participate in important developmental and physiological processes, but little is known about NF-YB proteins in trees. Here, we identified seven NF-YB transcription factor-encoding genes in Vernicia fordii, an important oilseed tree in China. A phylogenetic analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…All NF-Y subunits contain a highly conserved core region for subunit interactions, which are vital to the function of the transcription factor [ 3 ]. The NF-YB subunit includes an amino-terminal A domain, a B domain, and a carboxyl-terminal C domain [ 4 ]. Of these, the B domain is the most essential owing to the presence of amino acid residues necessary for its interaction with NF-YA and NF-YC [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All NF-Y subunits contain a highly conserved core region for subunit interactions, which are vital to the function of the transcription factor [ 3 ]. The NF-YB subunit includes an amino-terminal A domain, a B domain, and a carboxyl-terminal C domain [ 4 ]. Of these, the B domain is the most essential owing to the presence of amino acid residues necessary for its interaction with NF-YA and NF-YC [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, NF-YB genes have been shown to be involved in the process of chloroplast biogenesis in rice, and fruit ripening in the tomato [ 10 , 12 , 24 ], while the over-expression of a single NF-YB gene in wheat resulted in a 20–30% increase in grain yield [ 25 ]. In another study, VfNF-BY genes have been shown to play a vital role in pathogen response in the tung tree [ 4 ]. Even though NF-YB genes have been identified and characterized in dozens of plant species, the members and roles of this gene family in cotton, most notably in upland cotton ( G. hirsutum) , remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…After this infection process, the plants were cultivated in an artificial climate chamber (8 h light/16 h dark) at 26°C with 95% relative humidity. The plants were observed regularly and the disease incidence was recorded [ 30 ]. Roots of plants were collected, and the stage of infection was determined according to the symptoms of the seedlings.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, plant genes encoding the NF-YB subunit are expanded, such as 34 NF-YB genes in wheat [4] and more than 10 in Arabidopsis, Z. jujuba and rice [5][6][7]. The NF-YB subunit consists of three domains, including aminoterminal A domain, a central conserved B domain and carboxyl-terminal C domain [8]. Of these, the B domain contains the amino acid residues necessary for interaction with NF-YA and NF-YC [8,9], and according to whether the B domain contains 16 amino acid residues (MIRHDIYNDRQTAEKT) [10,11] or not, the NF-YB subunits are classified into either LEAFY COTYLEDON1(LEC1) or non-LEC1 types.…”
Section: Introductionmentioning
confidence: 99%
“…The NF-YB subunit consists of three domains, including aminoterminal A domain, a central conserved B domain and carboxyl-terminal C domain [8]. Of these, the B domain contains the amino acid residues necessary for interaction with NF-YA and NF-YC [8,9], and according to whether the B domain contains 16 amino acid residues (MIRHDIYNDRQTAEKT) [10,11] or not, the NF-YB subunits are classified into either LEAFY COTYLEDON1(LEC1) or non-LEC1 types. Some studies have suggested that the non-LEC1 NF-YB genes may evolve from duplication and functional divergence of LEC1 NF-YB genes [12][13][14].…”
Section: Introductionmentioning
confidence: 99%